2021
DOI: 10.3390/heritage4030091
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Dyes of Pre-Columbian Andean Textiles: Comparison of Ambient Ionization Mass Spectrometry and HPLC-DAD

Abstract: The complex and colorful textiles of ancient Peru have long been a focus of technical study, particularly to characterize the sources of the wide variety of dyes utilized by these Andean artisans. This manuscript describes the characterization of the dyes of both primary (red, blue, and yellow) and secondary (purple, orange, and green) colors sampled from textiles spanning five major civilizations: the Paracas Necropolis, the Nazca, the Wari, the Chancay, and the Lambayeque, all from Peru. All but the Paracas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…This can be proven by the chromatogram results that appear at different retention times (RT) with the standard and spike solutions and the wavelengths produced by different samples with standard and spike solutions. So it can be concluded that cosmetic hair dye preparations do not contain Acid Red 73, and this hair dye preparation is safe to use [97][98][99][100].…”
Section: Resultsmentioning
confidence: 95%
“…This can be proven by the chromatogram results that appear at different retention times (RT) with the standard and spike solutions and the wavelengths produced by different samples with standard and spike solutions. So it can be concluded that cosmetic hair dye preparations do not contain Acid Red 73, and this hair dye preparation is safe to use [97][98][99][100].…”
Section: Resultsmentioning
confidence: 95%
“…In diesem Zuge kommen vermehrt ambiente MS-Techniken zum Einsatz, beispielsweise DESI (desorption electrospray ionization), (droplet-)LMJ-SSP (liquid microjunction surface sampling probe) oder DART (direct analysis in real time). [20][21][22][23] Sie ermöglichen eine schnelle, minimal-invasive und zum Teil ortsaufgelöste Analyse von Verbindungen direkt von der Oberfläche der historischen Objekte, wobei die Untersuchungen wenig oder keine Probenvorbereitung benötigen und unter Atmosphärendruck erfolgen können. So lassen sich etwa historische Textilproben mit DESI-MS weitestgehend zerstörungsfrei und ohne vorhergehende Offline-Extraktion auf organische Farbstoffe analysieren (Abbildung 4).…”
Section: Ein Bild Sagt Mehr Als Tausend Worteunclassified
“…Finally, specific attention to dyed textiles is given in the contributions by Campos Ayala et al [16] and Łucejko et al [17]. In their article, Campos Ayala et al address the characterisation of the dyes used to produce primary (red, blue, and yellow) and secondary (purple, orange, and green) colours in Peruvian textiles spanning five major civilizations: the Paracas Necropolis, the Nazca, the Wari, the Chancay, and the Lambayeque [16].…”
Section: Sotiropoulou Et Al's Reviewmentioning
confidence: 99%
“…Finally, specific attention to dyed textiles is given in the contributions by Campos Ayala et al [16] and Łucejko et al [17]. In their article, Campos Ayala et al address the characterisation of the dyes used to produce primary (red, blue, and yellow) and secondary (purple, orange, and green) colours in Peruvian textiles spanning five major civilizations: the Paracas Necropolis, the Nazca, the Wari, the Chancay, and the Lambayeque [16]. With the intention to validate the use of ambient ionisation MS techniques, such as direct analysis in real time (DART-MS) and paper spray MS, the authors report on the results obtained from both reference samples and archaeological textiles, thus providing the reader with an important database.…”
Section: Sotiropoulou Et Al's Reviewmentioning
confidence: 99%